PFM.33 Estimating Maceration Severity Using Whole Body Magnetic Resonance T2 Relaxometry. (9th June 2014) - Lally, PJ; Arthurs, O; Addison, S; Alavi, A; Sebire, NJ; Taylor, A; Thayyil, S
Abstract : Background: Magnetic resonance (MR) imaging is an ideal modality to observe gross global changes in tissue structure, as is present with maceration. As tissue degrades, its MR transverse relaxation time (T2) should increase, with relaxometry methods enabling quantitative measurement of this. Objective: To use T2 relaxometry to non-invasively classify maceration and compare this with the assessment of a pathologist. Design/Methods: We performed post-mortem imaging in foetuses and neonates at 1.5T (Siemens Avanto). T2 relaxometry was performed using an eight-echo turbo spin echo sequence (TR = 2400 ms, TE = 44/88/132/176/220/264/308/352 ms), with even-echo images fitted to a mono-exponential decay function. Voxel-wise T2 values were generated from the model fit in each voxel to generate quantitative T2 maps, on which the lungs and liver were delineated (as shown in the figure ). Mean T2 values in each region were evaluated against global pathology maceration scores (1 to 4; none to severe) based on findings of paediatric pathologists at autopsy. Results: T2 was increased in both the lungs and liver for maceration scores of 3 or 4, when compared to those with grades 1 and 2. However, T2 also correlated inversely to the gestational age at death. Conclusions: Increasing maceration is associated with the prolongation of T2 values in the liver and lungs, but limitations arise due to conflation with gestational age effects, as younger foetuses were more macerated. T2 dependencies on gestational age are provided in the liver and lungs, allowing optimisation of post-mortem imaging for future studies.